Lepidaploa bracteospinoflava: a new Asteraceae gem in the biodiversity of Atlantic Forest in Rio de Janeiro, Brazil - DANILO MARQUES; ARISTÔNIO M. TELES; MARCELO MONGE; NÁDIA ROQUE (Anais da Academia Brasileira de Ciências)
Abstract Lepidaploa bracteospinoflava is a new species of Asteraceae from the Atlantic Forest in Rio de Janeiro, Brazil. The species was discovered in the high-altitude grasslands of Desengano State Park. It is characterized by the whitish sericeous on the abaxial leaf surface with prominent yellowish veins and involucral bracts with yellowish spines. We presented morphological comparisons among closely related species within the genus Lepidaploa, a dichotomous identification key for species in Rio de Janeiro state, illustrations, and a geographic distribution map. Lepidaploa bracteospinoflava is critically endangered due to its limited distribution, with an Area of Occupancy (AOO) of 3.000 km². The species is known from a single location, making it highly vulnerable to habitat loss and climate change. Field expeditions in Desengano State Park and surrounding areas are encouraged to locate additional populations. This discovery highlights the importance of continued botanical exploration and conservation efforts in critical biodiversity hotspots in Brazil.